2020
DOI: 10.1021/acs.inorgchem.0c02011
|View full text |Cite
|
Sign up to set email alerts
|

Selective Separation and Coordination of Europium(III) and Americium(III) by Bisdiglycolamide Ligands: Solvent Extraction, Spectroscopy, and DFT Calculations

Abstract: Diglycolamide-based ligands have recently received increased attention due to their outstanding affinity for trivalent actinides and lanthanides. The structure optimization of the ligands, however, still remains a hot topic to achieve better extraction performance. In this work, we prepare and investigate three multidentate diglycolamide ligands for the selective separation of Eu­(III) over Am­(III) from a nitric acid solution to explore the effect on the extraction of alkyl groups on the nitrogen atoms in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, it is extremely difficult to separate Ans­(III) from Lns­(III) efficiently and conveniently. It is believed that the separation of Lns­(III) and Ans­(III) with specifically designed ligands is an efficient and convenient method. , Researchers have developed a series of ligands and studied their applications in the separation of Lns­(III) and Ans­(III), such as trialkylphosphine oxide (TRPO), , N,N,N′,N′ -tetraoctyl diglycolamide (TODGA), , and di­(2-ethylhexyl)­phosphoric acid (HDEHP). Due to the demand for the “CHON” principle and high selectivity, nitrogen heterocyclic ligands, , such as 2,6-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-pyridine (BTP), 6,6′-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-2,2′-bypyridine (BTBP), , and 2,9-bis­(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen), are considered to be the most promising ligands for research and application. Therefore, to design a potential ligand to separate Ans­(III) over Lns­(III) with high efficiency and selectivity, our laboratory has successfully synthesized and characterized a novel lipophilic ligand, Et-Tol-DAPhen, which is applied in the selective separation of actinides over Eu­(III) in a highly acidic environment. …”
Section: Introductionmentioning
confidence: 99%
“…However, it is extremely difficult to separate Ans­(III) from Lns­(III) efficiently and conveniently. It is believed that the separation of Lns­(III) and Ans­(III) with specifically designed ligands is an efficient and convenient method. , Researchers have developed a series of ligands and studied their applications in the separation of Lns­(III) and Ans­(III), such as trialkylphosphine oxide (TRPO), , N,N,N′,N′ -tetraoctyl diglycolamide (TODGA), , and di­(2-ethylhexyl)­phosphoric acid (HDEHP). Due to the demand for the “CHON” principle and high selectivity, nitrogen heterocyclic ligands, , such as 2,6-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-pyridine (BTP), 6,6′-bis­(5,6-dialkyl-1,2,4-triazin-3-yl)-2,2′-bypyridine (BTBP), , and 2,9-bis­(1,2,4-triazin-3-yl)-1,10-phenanthroline (BTPhen), are considered to be the most promising ligands for research and application. Therefore, to design a potential ligand to separate Ans­(III) over Lns­(III) with high efficiency and selectivity, our laboratory has successfully synthesized and characterized a novel lipophilic ligand, Et-Tol-DAPhen, which is applied in the selective separation of actinides over Eu­(III) in a highly acidic environment. …”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that N,O-donor ligands were characterized by fast extraction kinetics 23,59,60 in terms of "test-tube" kinetics. In this work, extraction was carried out in a Lewis cell (see 2.4) with a constant stirring speed of each phase and with a stationary interface.…”
Section: Kinetics Studiesmentioning
confidence: 99%
“…Complexation of a REE ion with ligands is typically highly enthalpically favorable, and when calculated computationally yields a large negative energy of complexation, DF complex . [30][31][32][33] What is not captured by this approach are the positive DF contributions that can counteract the complexation favorability, a critical one being assembly of ligands into a geometry favorable for ion coordination, which necessarily occurs within a diluent. This is the DF assembly seen in Fig.…”
Section: Introductionmentioning
confidence: 99%